Does it go to right address to measure amniotic fluid DAMTS4, ADAMTS5, interleukin-6 and tumor necrosis factor-? without an ELISA assay validation? - Aydin, Suleyman; Ugur, Kader; Akkoc, Ramazan Fazil (Wiley, 2019)
[Abstract Not Available]